Complementary integrative approach for treating pruritus. Issue 2 (3rd April 2013) - Pfab, F.; Schalock, P. C.; Napadow, V.; Athanasiadis, G. I.; Yosipovitch, G.; Ring, J.
Abstract Complementary and alternative medicine (CAM) is a conservative and increasingly popular approach to treat pruritus for both patients and medical providers. CAM includes natural products, mind–body medicine, and manipulative and body‐based practices. In this overview, we summarize current evidence, possible mechanisms and clinical approaches for treating pruritus with CAM techniques. We focus on pruritus associated with atopic dermatitis, herpes zoster, chronic urticaria, burns, and postoperative contexts where the evidence for CAM approaches is promising.